The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3382/ps/pew437
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal betaine exposure modulates hypothalamic expression of cholesterol metabolic genes in cockerels through modifications of DNA methylation

Abstract: Cholesterol is essential for neuronal development and brain function. Previously we reported that in ovo administration of betaine modulates hepatic cholesterol metabolism in the chicken, yet it remains unknown whether maternal betaine affects the cholesterol content and the expression of cholesterol metabolic genes in chicken hypothalamus. In this study, eggs were injected with saline or betaine at 2.5 mg/egg, and the hatchlings were raised under the same condition until 64 d of age. Maternal betaine signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…We previously reported that supplementation of betaine could affect cholesterol metabolism in offspring by affecting carbon metabolism and DNA methylation ( Hu et al., 2015 , Idriss et al., 2017 , Zhao et al., 2019 ). In this study, maternal betaine supplementation significantly enhanced methionine metabolism and methyl transfer genes expression of BHMT, AHCYL, and DNMT1 at protein levels in the offspring chicken liver, which agrees with a previous finding that maternal betaine supplementation causes BHMT and DNMT1 upregulation in the hypothalamus of offspring cockerels ( Idriss et al., 2017 ). It is worth noting that, one carbon metabolism is essential for providing methyl group to the methylation of DNA, RNA, and histone methylation, thus playing a critical role in the epigenetic gene regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that supplementation of betaine could affect cholesterol metabolism in offspring by affecting carbon metabolism and DNA methylation ( Hu et al., 2015 , Idriss et al., 2017 , Zhao et al., 2019 ). In this study, maternal betaine supplementation significantly enhanced methionine metabolism and methyl transfer genes expression of BHMT, AHCYL, and DNMT1 at protein levels in the offspring chicken liver, which agrees with a previous finding that maternal betaine supplementation causes BHMT and DNMT1 upregulation in the hypothalamus of offspring cockerels ( Idriss et al., 2017 ). It is worth noting that, one carbon metabolism is essential for providing methyl group to the methylation of DNA, RNA, and histone methylation, thus playing a critical role in the epigenetic gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol and its metabolites are implicated in the pathogenesis of various human diseases, including atherosclerosis, cancer, neurodegenerative diseases, and non-alcoholic fatty liver disease ( Wu et al., 2013 , Coisne et al., 2016 , Van den Berg et al., 2018 , Ou et al., 2019 ). In the chicken, cholesterol metabolism in the brain and muscle was associated with aggressive behavior and meat quality, respectively ( Attia et al., 2017 , Idriss et al., 2017 ). Importantly, cholesterol level in the liver is an indicator of chicken fatty liver syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA, genomic DNA, and total protein were isolated from ground chicken hypothalamic samples, and Methylated DNA Immune Precipitation ( MeDIP ) assay was hired to observe the CpG methylation status on the promoter sequences of corresponding genes. Detailed protocols are the same as those described in our previous article ( Idriss et al., 2017 ). To be clear, all of the primers used for quantitative real-time PCR are listed in the first part of Table 1 , and the primers used for MeDIP assay are marked with “- promoter” tails.…”
Section: Methodsmentioning
confidence: 99%
“…Also, feeding methyl-enriched diet exclusively to F0 boars significantly changed the carcass traits, gene expression and DNA methylation in F2 generation ( Braunschweig et al., 2012 ). Recently, we reported that in ovo administration of betaine modulated hypothalamic expression of cholesterol metabolism genes in chicken ( Idriss et al., 2017 ). However, it remains unknown whether this effect will continue to be transmitted to subsequent generations of chickens.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation level was analyzed by a multiplex PCR and next-generation sequencing-based targeted CpG methylation analysis method-MethylTarget ™ (Genesky Biotechnologies Inc., Shanghai, China). The validity and reliability of this method have been previously reported [22][23][24]. Specifically, CpG islands located in the promoter of genes of interest were selected according to the following criteria: (1) 200 bp minimum length; (2) above 50% GC-content; (3) above 0.6 ratio of observed/ expected CpG.…”
Section: Dna Methylation Analysismentioning
confidence: 99%